JOB CREATION LAW AND ITS IMPACT ON THE ENVIRONMENT AND WORKERS' RIGHTS: A DESCRIPTIVE STUDY - Suryaningsi, Suryaningsi; Wulandari, Melda Nur; Hafida, Khoirunisa; Nila, Nila; Aditiyawan, Haris Rizky (Fakultas Hukum Universitas Swadaya Gunung Jati, 2025)
Law Number 11 of 2020 concerning Job Creation is presented as a solution to accelerate national economic growth by simplifying regulations. However, this policy caused controversy because it was perceived as compromising environmental protection and undermining workers' rights. This study aims to systematically describe the impacts of these regulations on two crucial aspects: the environment and employment. Using a qualitative descriptive method, the study's results show that the Job Creation Law leads to the easing of environmental regulations and increased labor flexibility, which has the potential to harm workers. The discussion centered on analyzing policy consequences and the importance of striking a balance between economic development and ecological and social justice.